Dietary vitamin K intake is associated with decreased neurofilament light chain among middle-aged and older adults from the NHANES - Luo, Jing; Lin, Song (Frontiers in Nutrition, 2024)
Purpose: Neurofilament-light chain (NfL) is associated with neurodegenerative diseases, which are increasingly prevalent with aging. Vitamin K has been shown a neuroprotective effect. Therefore, we aimed to explore the potential relationship between dietary vitamin K intake and serum NfL. Methods: This study was conducted on the 2013–2014 cycles of the National Health and Nutrition Examination Survey, a multi-site population-based study of the US general population. Serum NfL level was measured using a highly sensitive immunoassay. Dietary vitamin K intake was estimated from two-day dietary recall interviews, and its relationship with NfL was determined using linear regression models. Results: The study included a total of 1533 participants with a median age of 46 years, comprising 801 women (52.2%) and 732 men (47.8%). The median dietary intake of vitamin K was 81.6 µg/d, and the median serum NfL was 12 pg/ml. After adjusting for potential confounding factors in the full model, individuals with higher dietary vitamin K intake had lower serum NfL levels (Q4 vs Q1, β = −4.92, 95%CI: −7.66, −2.19, P = 0.002). A non-linear negative dose-response association is found between dietary vitamin K intake and serum NfL levels (P for non-linearity = 0.008); this association reaches a plateau when the dietary vitamin K intake is higher than 200 µg/d. According to the results of stratified analysis, the relationship between dietary vitamin K intake and serum NfL levels was stronger in the population of middle-aged and older adults. Conclusion: The present study suggested a negative association between dietary vitamin K intake and serum NfL levels in the general US population, especially in middle-aged and older adults. This study might offer a novel nutritional idea for the primary prevention and mechanism exploration of neurodegenerative diseases.